Caribbean migration to Western Europe and the United States : essays on incorporation, identity, and citizenship - Cervantes-Rodríguez, Ana Margarita; Grosfoguel, Ramón; Mielants, Eric (Temple University Press, 2009)
A novel and interdisciplinary volume on the dynamics of migration with comparative case studies of the Caribbean experience.